The fundamentals of typography - Ambrose, Gavin; Harris, Paul 1971-; Theodosiou, Sallyanne (Bloomsbury Visual Arts, 2020)
This book introduces the fundamental principles of typographic theory and practice. It covers a wide range of subjects including the history of typography, typographic detailing, and the use of creative typography across a range of media. It is packed with clear explanations, expanded illustrations, and historical and contemporary examples from leading practitioners around the world. The second edition includes considerable new and revised content and includes new case studies and student exercises.